Reading Achievement of Deaf Students: Challenging the Fourth Grade Ceiling. (1st June 2021) - Mayer, Connie; Trezek, Beverly J; Hancock, Gregory R
Abstract: Historically it has been reported that deaf students do not achieve age-appropriate outcomes in reading, with this performance often being characterized in terms of a fourth grade ceiling. However, given the shifts in the field during the past 20 years (e.g., widespread implementation of newborn hearing screening, advances in hearing technologies), it would be timely to question whether this continues to serve as a meaningful benchmark. To this end, the purpose of this study was to investigate reading outcomes of a Canadian cohort of school-aged deaf learners ( N  = 70) who all used listening and spoken language as the primary mode of communication. Specifically, the goal was to establish whether their achievement approached that of their hearing age peers and to identify demographic factors influencing performance (i.e., gender, unilateral/bilateral hearing loss, personal amplification, level of auditory functioning, grade placement, additional disabilities, home language). Results indicate that participants obtained standard scores in the average range on both the Basic Reading and Reading Comprehension clusters of the Woodcock Johnson III-Diagnostic Reading Battery (Woodcock et al., 2004), surpassing the fourth grade reading achievement ceiling often reported for this population.